Endoplasmic Reticulum Stress: An Emerging Therapeutic Target for Intervertebral Disc Degeneration - Wang, Dong; He, Xin; Zheng, Chao; Wang, Chengzhe; Peng, Pandi; Gao, Chu; Xu, Xiaolong; Ma, Yachao; Liu, Mei; Yang, Liu; Luo, Zhuojing (Frontiers in Cell and Developmental Biology, 2022)
Low back pain (LBP) is a global health issue. Intervertebral disc degeneration (IDD) is a major cause of LBP. Although the explicit mechanisms underpinning IDD are unclear, endoplasmic reticulum (ER) stress caused by aberrant unfolded or misfolded proteins may be involved. The accumulation of unfolded/misfolded proteins may result in reduced protein synthesis and promote aberrant protein degradation to recover ER function, a response termed the unfolded protein response. A growing body of literature has demonstrated the potential relationships between ER stress and the pathogenesis of IDD, indicating some promising therapeutic targets. In this review, we summarize the current knowledge regarding the impact of ER stress on the process of IDD, as well as some potential therapeutic strategies for alleviating disc degeneration by targeting different pathways to inhibit ER stress. This review lays the foundation for understanding the pathogenesis and progress of IDD and highlights potential therapeutic targets for treating this condition.